2010
DOI: 10.1002/hrm.20367
|View full text |Cite
|
Sign up to set email alerts
|

Is internationalization associated with investments in HRM? A study of entrepreneurial firms in emerging markets

Abstract: This study investigates how internationalization is associated with investing in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 111 publications
(127 reference statements)
1
60
1
3
Order By: Relevance
“…Rather, the diffusion from some of the Western hosts to the HQ was indirect through the consultancy firms as opposed to directly through the MNE. Second, our findings seem at odds with previous research that suggests that EM-MNEs apply different HR practices in developed country subsidiaries and developing country subsidiaries (Khavul et al, 2010). We have specifically put this question to interviewees, but not a single interviewee hinted at such a distinction.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Rather, the diffusion from some of the Western hosts to the HQ was indirect through the consultancy firms as opposed to directly through the MNE. Second, our findings seem at odds with previous research that suggests that EM-MNEs apply different HR practices in developed country subsidiaries and developing country subsidiaries (Khavul et al, 2010). We have specifically put this question to interviewees, but not a single interviewee hinted at such a distinction.…”
Section: Discussioncontrasting
confidence: 66%
“…Given that previous research suggested that emerging market MNEs apply different HR practices in developed country subsidiaries and developing country subsidiaries (Khavul, Benson, & Datta, 2010) and given that there may be differences in terms of forward diffusion and reverse diffusion between developed country subsidiaries and developing country subsidiaries, our research design purposively includes interviews with both a developed country subsidiary and with a developing country subsidiary for each company. The key characteristics of interviewed subsidiaries are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, HRM practices of MNEs will be influenced by their home country national business systems and tend to exhibit distinctive internationalization paths (Ferner and Quintanilla 1998;Ngo et al 1998;Gamble 2003). Tymon et al (2010) and Khavul et al (2010) indicate that the vestiges of British colonial rule still remain in India and the evolution of the Indian HRM function has mirrored that of Britain, shifting from an emphasis on personnel towards a more strategic HR role but with a greater emphasis on human resource development (Budhwar and Varma 2010). Cooke and Saini (2010) suggest that Indian managers mirror their Western counterparts in their selection of HRM practices that promote innovation in organisations, with practices including training and development, performance appraisals, staff suggestion schemes.…”
Section: Country Of Origin Effect and The African Contextmentioning
confidence: 99%
“…A mixture of developments such as rapid globalization, the rise of emerging markets, technological developments, constant change and the emergence of intellectual capital as a key sustainable competitive advantage requires the HR function to be ever more strategic and global in its role, outlook and approach (Briscoe, Schuler & Tarique, 2011;Chung, Bozkurt & Sparrow, 2012;Khavul, Benson & Dutta, 2010). In such a context, corporate HR plays a prominent role in the management of the global workforce in MNCs (Farndale, Scullion & Sparrow, 2010a;Farndale, Paauwe, Morris et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%